(3-methyl-3-phenylcyclobutyl)(naphtho[2,1-b]furan-2-yl) methanone - Arici, Cengiz; Kirilmis, Cumhur; Koca, Murat; Heinemann, Frank W. (Blackwell Publishing, 2006)
In the title compound, C24H20O2, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi-pi interactions result in a three-dimensional supramolecular network.